Spectrally encoded extended source optical coherence tomography - Yu, Xiaojun (2015)
We have developed an extended source optical coherence tomography (SEES-OCT) technique in an attempt to improve signal strength for ophthalmic imaging. A line illumination with a visual angle of 7.9 mrad is produced by introducing a dispersive element in the infinity space of the sample arm. The maximum permissible exposure (MPE) of such an extended source is 3.1 times larger than that of a ‘standard’ point source OCT, which corresponds to sensitivity improvement of 5-dB. The advantage of SEES-OCT in providing superior penetration depth over a point source system is demonstrated using swine eye tissues ex vivo.